METHOD DEVELOPMENT AND VALIDATION OF CEFOPERAZONE AND SULBACTAM IN DRIED BLOOD SPOTS BY HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY PHOTODIODE ARRAY DETECTOR - PERMATA, DIAN; HARAHAP, YAHDIANA; RAMADON, DELLY (International Journal of Applied Pharmaceutics, 2022)
Objective: The primary purpose of this research was to develop a simple, precise, fast, and accurate method for measuring cefoperazone and sulbactam simultaneously in dried blood spots (DBS) using HPLC PDA. Methods: A simplified analytical method for quantifying cefoperazone and sulbactam in DBS samples using a High-Performance Liquid Chromatography photodiode array detector with isocratic elution was developed and validated. The best chromatographic conditions were obtained by using a reversed-phase column (250 x 4.6 mm; 5 mm); phosphate buffer 10 mmol pH 3.2–acetonitrile (83:17, v/v) as a mobile phase; a flow rate of 1.0 ml/min; a column temperature of 35 °C; a photodiode array detector at 210 nm, and cefuroxime as internal standard. Samples were prepared by liquid-liquid extraction with 100 ml hydrochloric acid 0.5 mol/l and 1000 ml ethyl acetate, evaporated with nitrogen and reconstituted with 100 mL phosphate buffer–acetonitrile (4:1). Results: The total chromatography run time was 15 min, and the elution times for sulbactam, cefoperazone, and IS (cefuroxime) were 3.46, 10.221, and 6.987 min, respectively. A linear response function was established at 0.5-30 mg/ml with (r) 0.995 for sulbactam and 2.5-250 mg/ml with (r) 0.999 for cefoperazone in dried blood spots. The lower limit quantification (LLOQ) concentration of sulbactam 1 mg/ml and cefoperazone were 5 mg/ml. Conclusion: This method has successfully fulfilled the validation requirement referring to the 2011 EMA and 2018 FDA guidelines.